Role of Cryoablation for the Treatment of cT1b Kidney Lesions: Outcomes of a Systematic Review - Adnan El-Achkar; Mustafa Khader; Ala'a Farkouh; Joelle Hassanieh; Bhaskar Somani; Mohammed Shahait (Société Internationale d’Urologie Journal)
IntroductionThe American Urological Association (AUA) and the European Association of Urology (EAU) currently recommend partial nephrectomy (PN) over ablation for cT1b lesions. However, recent series have shown comparable outcomes for cryoablation (CA) when compared to PN, making it an appealing alternative for a select group of patients. The objective of this manuscript is to assess treatment outcomes and complications of CA for cT1b lesions. MethodsUsing Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a comprehensive search was done on MEDLINE and Cochrane Library electronic databases identifying studies that reported on outcomes and complications of CA for kidney tumors. Inclusion criteria included cT1b lesions between 4 cm and 7 cm, excluding treatment of other sizes. ResultsA total of 347 patients with cT1b lesions identified on imaging underwent percutaneous or laparoscopic CA. The average age was > 65 years, the median size of lesions and RENAL score ranged between 4.3–4.8 cm and 8–9, respectively. The majority of patients had a Charlson comorbidity index (CCI) of 2, and median follow-up ranged between 13 months and 95 months. Across all the series, primary and secondary success rates were between 84%–98% and 92%–98%, respectively. The local recurrence ranged from 2.8% to 27%. For patients with documented RCC on biopsy, the 5-year overall survival (OS), cancer-specific survival (CSS), recurrence-free survival (RFS), and metastasis-free survival (MFS) ranged from 56%–91%, 85%–100%, 70%–96.4%, and 90%–96%, respectively. The major complication rate (Clavien-Dindo III-V) was low, at 6.2%. ConclusionWith promising survival outcomes and low complication rates perioperatively, CA is acceptable in a select group of patients with T1b renal tumors, including those who are older, have multiple comorbidities, or have relative or absolute contraindication to surgery.